PENGARUH STRUKTUR MODAL, INFLASI, DAN BEBAN CUKAI TERHADAP KINERJA KEUANGAN PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Sofia Masytha Salsabila; Dyah Rini Prihastuty (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the effect of capital structure, inflation, and excise tax burden on the financial performance of cigarette companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employs a quantitative approach using multiple linear regression analysis. Capital structure is proxied by the Debt to Equity Ratio (DER), inflation is measured using the annual Consumer Price Index, and excise burden is calculated as the proportion of excise costs to company revenue. Financial performance is proxied by Net Profit Margin (NPM). The sample consists of four cigarette companies: PT Hanjaya Mandala Sampoerna Tbk, PT Gudang Garam Tbk, PT Wismilak Inti Makmur Tbk, and PT Indonesian Tobacco Tbk. The results show that capital structure, inflation, and excise burden simultaneously have a significant effect on financial performance. Partially, capital structure and inflation have a negative effect on NPM, while excise burden has the most dominant negative effect. These findings indicate that fiscal policy and macroeconomic conditions play a crucial role in determining the profitability of the cigarette industry in Indonesia